Evaluation of the Center of Excellence Vocational High School Partnership Model in Increasing Resilience and Competitiveness - Faris Fanani; Rusdarti Rusdarti; Dwi Yuwono Puji Sugiharto; Arief Yulianto (International Conference on Science, Education, and Technology, 2023)
Education is experiencing very rapid and complex changes in science and technology as a result of the industrial era 4.0 and society 5.0 which requires life skills consisting of four types of skills. Center of Excellence Vocational School as a vocational education institution based on the independent learning program has an obligation to produce graduates who are resilient and competitive in the global era. The purpose of this research is to find out how the implementation of the partnership model used by Vocational High School centers of excellence can be evaluated to prepare graduates who are resilient and globally competitive. This study uses a qualitative descriptive method to collect information from primary sources, namely the management of the Center for Excellence Vocational High School in Semarang City, Central Java, Business and Industry Sector partners and other supporting sources in the form of documents. The results of this study indicate that the Center for Excellence Vocational High School conducts a partnership pattern with business and industry to improve the quality of graduates. tough and competitive. This research will benefit the Center of Excellence Vocational High Schools to carry out partnership innovations with Business and Industry Sector which have a positive impact on the quality of tough and competitive graduates, thereby affecting the level of absorption of graduates in the world of work in the era of society 5.0